Risk factors for the presence of important fractures in ED patients with shoulder dislocation: a retrospective cohort study. Issue 9 (17th February 2022) - Delattre Sousa, Salomé; Houze-Cerfon, Charles Henri; Le Gourrierec, Thibault; Charpentier, Sandrine; Dubucs, Xavier; Balen, Frederic
Abstract : Background: Prereduction shoulder X-rays are frequently done to rule out an important fracture that might preclude reduction of a shoulder dislocation in the ED. Our objective was to determine the risk factors for an important fracture in patients admitted to the ED with shoulder dislocation. Methods: This retrospective cohort study was conducted at the Toulouse University Hospital from 1 January 2017 to 31 December 2018. All patients admitted to the ED with clinical presentation of shoulder dislocation were included. The primary end point was the presence of an important fracture (excluding Bankart and Hill-Sachs fractures). Logistic regression was used to determine independent risk factors for the presence of an important fracture. Results: Six hundred and two patients were included in the study and 81 (13%) had an important fracture. Three risk factors were associated with important fracture: age over 40 years (adjusted OR (aOR)=2.7; 95% CI 1.5 to 4.8), first incident (aOR=4.3; 95% CI 1.7 to 10.8) and the circumstances in which the trauma occurred (fall from a height or direct impact, fall of over 1 m, road accident or epilepsy) (aOR=5.5; 95% CI 2.6 to 30). One hundred sixty-six patients (28%) had no risk factors in our cohort. In the absence of these risk factors, the risk of an important fracture was found to be 0.6% (95% CI 0 to 3.3). Conclusion: We describe 3 independent clinical risk factors associated with an important fracture in ED patients with shoulder dislocation: age >40 years, first incident and a traumatic circumstance. Prereduction radiography may be safely avoided when these factors are absent.